1998
DOI: 10.1046/j.1432-1327.1998.2530771.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen‐regulated erythropoietin gene expression is dependent on a CpG methylation‐free hypoxia‐inducible factor‐1 DNA‐binding site

Abstract: The hypoxia-inducible factor-1 (HIF-1) is a transcriptional activator involved in the expression of oxygen-regulated genes such as that for erythropoietin. Following exposure to low oxygen partial pressure (hypoxia), HIF-1 binds to an hypoxia-response element located 3′ to the erythropoietin gene and confers activation of erythropoietin expression. The conserved core HIF-1 binding site (HBS) of the erythropoietin 3′ enhancer (CGTG) contains a CpG dinucleotide known to be a potential target of cytosine methylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
108
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(114 citation statements)
references
References 34 publications
5
108
0
1
Order By: Relevance
“…47 Thus the promoter region of EPO is a target for ischemia-mediated hypomethylation as an adaptive mechanism in ischemic tissue. There are several other genes involved in adaptation to ischemia which utilize the HIF1 pathway, such as vascular endothelial growth factor (VEGF) and inducible nitric oxide synthase (iNOS).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Thus the promoter region of EPO is a target for ischemia-mediated hypomethylation as an adaptive mechanism in ischemic tissue. There are several other genes involved in adaptation to ischemia which utilize the HIF1 pathway, such as vascular endothelial growth factor (VEGF) and inducible nitric oxide synthase (iNOS).…”
Section: Methodsmentioning
confidence: 99%
“…There are several other genes involved in adaptation to ischemia which utilize the HIF1 pathway, such as vascular endothelial growth factor (VEGF) and inducible nitric oxide synthase (iNOS). 47 We have demonstrated that the tumor microenvironment may be an important modulator of DNMT expression and the effects of ischemia on global methylation and expression changes in human colorectal cancer are currently being investigated. The impact of agents which modulate the tumor (1:250; Imgenex) over night at 4°C followed by goat anti-mouse Cy3 (1:200; Jackson Immunoresearch, West Grove, PA, USA) for 1 h at 22°C.…”
Section: Methodsmentioning
confidence: 99%
“…This is evident in the erythropoietin and the class III beta-tubulin genes, where it has been shown that hypoxia-induced expression is dependent upon the tissuespecific methylation status of a HRE in the 3'-UTR. [17][18][19] As global changes in DNA methylation can occur under chronic hypoxic conditions, it is possible that this may impact on the methylation status of HRE sites, 1,20 and thus shape the HIF-dependent transcriptional profile according to the intensity and duration of the hypoxic insult. Gene specific DNA hypomethylation may reveal previously inaccessible HIF binding sites, thus exposing new active regions for HIF or other hypoxia-responsive transcription factors.…”
Section: Methylation In Hypoxiamentioning
confidence: 99%
“…These results indicated that only a part of HRE motifs had an open nucleosome structure suitable for subsequent transcriptional activation, although HRE motifs were present throughout the human genomic sequences. Previous HIF-1a ChIP-chip studies have reported that less than 1% of the HRE motifs within the genomic sequences that are located in regions used for the microarrays are bound by HIF-1a (Mole et al 2009;Wenger et al 1998Wenger et al , 2005. Epigenetic regulation of the human genome plays an essential role in specifying the binding sites of HIF-1a in addition to the consensus binding sequences.…”
Section: Epigenetic Regulation In Regions Surrounding Hif-1a Binding mentioning
confidence: 99%